In Vitro Anti-Photoaging Properties of Phylanthus urinaria L. Herb Extract - Arsiningtyas, Ines Septi; Simamora, Desy Damayanti; Palimbongan, Angela Merici; Widianingtyas, Fabiana Disa; Junedi, Sendy (Indonesian Journal of Cancer Chemoprevention, 2024)
The overexposure to ultraviolet (UV) radiation from sunlight is related to photoaging of the skin and high risk of skin cancer. Sunscreen material and antioxidants are commonly used to protect skin from harmful UV. However, the application of synthetic compounds in sunscreen products is regulated to a limited amount because it can produce photosensitizers, inducing adverse reactions in the skin, and also harmful to the environment. Ethanol extract of Phyllanthus urinaria L. herb possesses a strong antioxidant activity similar to ascorbic acid, which makes it potential to substitute the synthetic compound in sunscreen products. Therefore, this research was conducted on the 70% ethanol extract of P. urinaria herb to analyze its in vitro anti-photoaging properties, i.e., antioxidant, protein antiglycation and antiinflammation, also to determine the Sun Protection Factor (SPF) and the quantitative composition of the metabolites. The extract exhibited a strong antioxidant activity IC50 of 3.01 mg/L, a higher moderate antiglycation activity IC50 of 216.67 mg/L, but low anti-inflammatory activity IC50 of 86.61mg/L. The presence of saponin, phenolic compounds, flavonoids, tannins, and methyl linoleates is suggested to contribute to the anti-photoaging properties. According to the anti-inflammatory assay, the extract may not inhibit signaling pathways that follow cytokine expression but possibly inhibit those that precede cytokine expression due to its antioxidant activity. An SPF value of 5.95 at 50 mg/L meets the recommended range for the skin phototypes of Southeast Asian, dark-skinned Asian, and African people. These results indicate that P. urinaria extract has potential as an anti-photoaging material for sunscreen products.Keywords: antiglycation, antiinflammation, antioxidation, Phyllanthus urinaria L., SPF.